Pension Saving Responses to Anticipated Tax Changes: Evidence from Monthly Pension Contribution Records - Claus Thustrup Kreiner; Søren Leth-Petersen; Peer Ebbesen Skov (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2016)
A Danish tax reform, decided in May 2009 and taking effect from the beginning of 2010, lowered the marginal tax rate on top bracket taxable income from 63% to 56%. Because contributions to pension accounts are tax deductible, the reform provided an incentive to increase pension contributions before the change in taxation. Using high frequency panel data, we document an increase in pension contributions in the second half of 2009 in response to the anticipated change in taxation, and that this led to an increase in total savings. Length: 36 pages
Keywords: H3; 330; Pension savings; tax incentives; high frequency individual data